Pengaruh Market Value dan Market Capitalization terhadap Return Saham Jakarta Islamic Indeks (JII) - Fransisca Putri Isabela; Gde Herry Sugiarto Asana; Sarita Vania Clarissa (Jurnal Widya Akuntansi dan Keuangan, 2024)
The main consideration in investing to get a profitable stock return. The rate of return on stocks is influenced by several factors, such as market value and market capitalization. The purpose of this study is to determine the effect of low market value, high market value, small market capitalization, and large market capitalization on stock returns in the Jakarta Islamic Index 2020-2022. This study uses associatives that show the relationship of the independent variable with the dependent variable. The sample of this study is companies listed in the Jakarta Islamic Index 2020-2022. The sampling used in this study used the Purposive Sampling method with certain criteria. Companies that can be used as samples are 20 companies that have met the sampling criteria so that 60 data samples are obtained. This research data uses secondary data sourced from the 2020-2022 financial statements. This study used multiple linear regression analysis. The results of this study show that low market value (PBV) variables and small market capitalization do not have a significant effect on stock returns, while high market value (PBV) and large market capitalization have a positive and significant effect on stock returns.